2024
DOI: 10.1186/s41235-023-00528-4
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and changes in social behavior: Protective face masks reduce deliberate social distancing preferences while leaving automatic avoidance behavior unaffected

Esther K. Diekhof,
Laura Deinert,
Judith K. Keller
et al.

Abstract: Protective face masks were one of the central measures to counteract viral transmission in the COVID-19 pandemic. Prior research indicates that face masks impact various aspects of social cognition, such as emotion recognition and social evaluation. Whether protective masks also influence social avoidance behavior is less clear. Our project assessed direct and indirect measures of social avoidance tendencies towards masked and unmasked faces in two experiments with 311 participants during the first half of 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A further limitation the present work is that we only relied on explicit reports about trait impressions from faces. There is some evidence that the presence (vs absence) of face masks may affect deliberate behavioral intentions but not necessarily more automatic responses (Diekhof et al, 2024 ), thus raising the question about whether the contextual modulations observed in the present studies can also be detected through tasks that assess less controlled responses (e.g., priming tasks; Wentura & Degner, 2010 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A further limitation the present work is that we only relied on explicit reports about trait impressions from faces. There is some evidence that the presence (vs absence) of face masks may affect deliberate behavioral intentions but not necessarily more automatic responses (Diekhof et al, 2024 ), thus raising the question about whether the contextual modulations observed in the present studies can also be detected through tasks that assess less controlled responses (e.g., priming tasks; Wentura & Degner, 2010 ).…”
Section: Discussionmentioning
confidence: 72%
“…Hence, we employed the same 5 traits included in Study 1 and 2 additional traits. Attractiveness and willingness to interact were included as further traits employed in relevant previous work about trait impressions from faces (e.g., Sutherland et al, 2013 ), and more specifically in several previous studies about the impact of face masks on impression formation (e.g., Diekhof et al, 2024 ; Hies & Lewis, 2022 ; Kühne et al, 2022 ; Oldmeadow & Koch, 2021 ). The presentation order of the faces was randomized.…”
Section: Methodsmentioning
confidence: 99%